Feminist Perspectives on Reproduction and Motherhood and/as Cultivation: Ruth Ozeki’s All Over Creation - Ina Batzke (European Journal of American Studies)
This article discusses women’s reproductive agency and/or suppression in connection with biotechnological innovations in the agricultural industry, especially genetically modified crops (GMOs). To do so, it takes up Ruth Ozeki’s creative response on this interconnection, the 2002 novel All Over Creation, which utilizes a fictional farmer community in Idaho to address broader cultural issues such as sexism, racism, and reproductive justice. The analysis shows how All Over Creation first and foremost succeeds via a multivocal narrative to create a feminist response to both neoliberal biotechnological enhancements and dominant cultural notions of fertility, reproduction, and motherhood. At the same time, this article neglects the utopian potential that critics and reviewers have attributed to the text, and instead reveals how such a reading not only ignores substantial aspects of the novel’s ideological complexity, but also unmasks a reader’s complicity with (hetero-)normative understandings of reproduction.